2015
DOI: 10.11591/ijece.v5i1.pp78-83
|View full text |Cite
|
Sign up to set email alerts
|

Feature Selection of the Combination of Porous Trabecular with Anthropometric Features for Osteoporosis Screening

Abstract: This study aims to select the important features from the combination of porous trabecular pattern with anthropometric features for osteoporosis screening. The study sample has their bone mineral density (BMD) measured at the proximal femur/lumbar spine using dual-energy X-ray absorptiometry (DXA). Morphological porous features such as porosity, the size of porous, and the orientation of porous are obtained from each dental radiograph using digital image processing. The anthropometric features considered are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 14 publications
1
17
1
2
Order By: Relevance
“…The condition of low bone mineral density may induce perforation on the trabecular bone of mandible that can be characterized by the increase of small areas in the radiograph. The result of this study is suitable for previous studies [10], [11], [14]. The previous study showed that periapical radiograph potential to be used as osteoporosis predictor using the parameter of length and the amount of strut on a particular region of the periapical radiograph.…”
Section: B Discussionmentioning
confidence: 51%
“…The condition of low bone mineral density may induce perforation on the trabecular bone of mandible that can be characterized by the increase of small areas in the radiograph. The result of this study is suitable for previous studies [10], [11], [14]. The previous study showed that periapical radiograph potential to be used as osteoporosis predictor using the parameter of length and the amount of strut on a particular region of the periapical radiograph.…”
Section: B Discussionmentioning
confidence: 51%
“…Regardless of whether bone mineral thickness (BMD) in subjects with a crack of the proximal femur (hip break) is not quite the same as that of age-coordinated controls is still discussed. This study [7] Main factors which are obtained by the combination of the porous trabecular schema along with the anthropometric highlights for osteoporosis screening. The examination test has their bone mineral thickness (BMD) estimated at the proximal femur/lumbar spine utilizing double vitality X-beam absorptiometry (DXA).…”
Section: A Causes Of Osteoporosismentioning
confidence: 99%
“…Osteoporotic bone alteration on the mandibular cortical bone is visible on panoramic radiograph and can be easily seen by a dentist. Whereas the mandible trabecular bone alterations related with osteoporosis also visible on periapical radiographs as well as panoramic radiographs [12], [16], [17]. The periapical radiography is a low-cost examination.…”
Section: Introductionmentioning
confidence: 99%
“…However, the result of the system may be influenced by observers' diagnostic performance [17]. Some previous studies showed that image analysis also can be applied in periapical radiograph to predict the osteoporosis condition [16]- [20]. The combination of BMD and texture parameter values reported to provide a better assessment of the fracture risk than that obtainable by BMD measurement only [21].…”
Section: Introductionmentioning
confidence: 99%